Design of Modified Release Multiunit Drug Delivery System for the Effective Treatment of Gastroesophageal Diseases using Hot-melt Coating - G. Sudke, Suresh (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The objective of the present investigation involves the design of modified release multiunit drug delivery system for the effective treatment of gastroesophageal diseases (GEDs) using hot-melt coating (HMC) technique. Materials and Methods: Ranitidine hydrochloride (R.HCL) pellets were prepared using extrusion-spheronization and coated with different levels of hydrogenated castor oil (HCO) as HMC agent using pan pour method. To achieve the desirable release profile, R.HCL pellets were coated with a hybrid of HCO and sodium lauryl sulfate as a pore former. The pellets were evaluated for micromeritic properties, physicochemical properties, in vitro buoyancy study, dissolution study, and stability study. Optimized formulation was selected by comparison of the drug release profiles with theoretical release profile (TRP). Results: Formulation R6 with low floating lag time, floating time >12 h, and the drug release profile similar to TRP. Therefore, R6 was selected as optimized formulation and molded into unit dosage form by filling the pellets in hard gelatin capsules. The R6 formulation shows significant performance in vitro. Optimized formulation was showed no significant difference in their micromeritic properties, physicochemical properties, in vitro buoyancy, and dissolution release after storing under 40°C ± 2°C temperature and 75% ± 5% relative humidity for 3 months. Conclusion: This study confirms the modified release potential of HCO by successfully designing of modified multiparticulate drug delivery system of R.HCL using HMC technique. This drug delivery system may prove effective for the treatment of GEDs by sustained drug release in absorption window for prolong period.